Ameliorating the Interfacial Problems of Cathode and Solid‐State Electrolytes by Interface Modification of Functional Polymers. Issue 24 (1st July 2018) - Wang, Li‐Ping; Zhang, Xu‐Dong; Wang, Tai‐Shan; Yin, Ya‐Xia; Shi, Ji‐Lei; Wang, Chun‐Ru; Guo, Yu‐Guo
Abstract: Solid‐state Li secondary batteries may become high energy density storage devices for the next generation of electric vehicles, depending on the compatibility of electrode materials and suitable solid electrolytes. Specifically, it is a great challenge to obtain a stable interface between these solid electrolytes and cathodes. Herein, this issue can be effectively addressed by constructing a poly(acrylonitrile‐ co ‐butadiene) coated layer onto the surface of LiNi0.6 Mn0.2 Co0.2 O2 cathode materials. The polymer layer plays a vital role in working as a protective shell to retard side reaction and ameliorate the contact of the solid–solid interface during the cycling process. In the resultant solid‐state batteries, both rate capacity (99 mA h g −1 at 3 C) and cycling stability (75% capacity retention after 400 cycles) are improved after coating. This impressive performance highlights the great importance of layer modification in the cathode and inspires the development of solid‐state batteries toward practical applications. Abstract : To mitigate the interfacial problems between cathode and solid electrolyte, a soft poly(acrylonitrile‐ co ‐butadiene) nanolayer is coated onto the cathode materials. The soft layer can not only sustain an admirable physical contact during cycling but also retard uncontrolled side reactions of the interface by shielding the particles from direct contact with the solid electrolyte.